Neonatal screening programme for CF: Results from the Irish Comparative Outcomes Study (ICOS). Issue 9 (16th June 2020) - Fitzgerald, Catherine; Linnane, Barry; George, Sherly; Ni Chroinin, Muireann; Mullane, David; Herzig, Mary; Greally, Peter; Elnazir, Basil; Healy, Fiona; Mc Nally, Paul; Javadpour, Sheila; Cox, Des; et al.
Abstract: The introduction of NBS in Ireland in July 2011, provided a unique opportunity to investigate clinical outcomes using a comparative historical cohort study. Clinical cohort: children clinically diagnosed with CF born 1 July 2008 to 30 June 2011, and NBS cohort: children diagnosed with CF through NBS born 1 July 2011 to 30 June 2016. Clinical data were collected from the CF Registry of Ireland, medical charts, and data on weight/height before diagnosis from public health nurses and family doctors. SPSS was used for analysis. A total of 232 patients were recruited (response 93%) (93 clinically diagnosed, 139 NBS‐detected). Following exclusions of meconium ileus (MI) (40), diagnosis outside Ireland (4), and being designated as CFSPID (2), a total of 77 clinically diagnosed patients and 109 NBS detected children were included in analysis. Over half were homozygous for F508del mutation. Being clinically diagnosed was independently associated with hospitalization for infective exacerbation of CF < 36 months (OR, 2.80; 95%CI 1.24‐6.29). Diagnosis to first acquisition of Pseudomonas aeruginosa was significantly longer in NBS than clinically detected; from birth there was no significant difference. Weight and length/height were significantly greater in NBS cohort at 6 and 12 months. We provide evidence of improved growth, reduced hospitalization for acute exacerbations, and delayed P. aeruginosa acquisition (from diagnosis) to age 3 for the NBS cohort. Screening practices likely account for the non‐significant difference in P. aeruginosa acquisition from birth.